2021 ACC/AHA Key Data Elements and Definitions for Heart Failure: A Report of the American College of Cardiology/American Heart Association Task Force on Clinical Data Standards (Writing Committee to Develop Clinical Data Standards for Heart Failure). Issue 4 (23rd March 2021) - Bozkurt, Biykem; Hershberger, Ray E.; Butler, Javed; Grady, Kathleen L.; Heidenreich, Paul A.; Isler, Maria Lizza; Kirklin, James K.; Weintraub, William S.
Abstract : Supplemental Digital Content is available in the text.